Timing recovery after the cretaceous/paleogene boundary: evidence from Brazos River, Texas - Leighton, Andrew D.; Hart, Malcolm B.; Smart, Christopher W.; Leng, Melanie J.; Hampton, Matthew (Cushman Foundation for Foraminiferal Research, 2017)
As part of an on-going re-assessment of the Cretaceous/ Paleogene boundary in the Brazos River area, Falls County, Texas, a number of new exposures have been described. One of these, at River Bank South, provides a near continuous record of the lowermost Paleocene. It is from this succession that stable isotope analysis of bulk organic matter (δ13C and C/N) and mono-specific samples of the benthic foraminifera Lenticulina rotulata Lamarck (δ18O and δ13C) yields an orbitally-tuned stable isotope record, which allows the timing of events adjacent to the Cretaceous/Paleogene boundary to be determined. Using this cyclicity, it is suggested that the on-set of biotic recovery began ∼40,000 years after the impact (near the base of Zone Pα) and that more significant recovery of planktic foraminifera and calcareous nannofossils began close to the base of Zone P1a, some 85,000–100,000 years post-impact. The data also appear to record the presence of the earliest Paleocene DAN-C2 and Lower C29n hyperthermal events and that these events appear to be an accentuated segment of this orbital cyclicity.